The Project Management in Alignment with the Sustainable Development Goals (SDGs): A Case Study of Schools selected as Best Practice in the CONNEXT ED Project - Maneeshote, Tiwat; Voravarn, Sornsiri; Tubtimcharoon, Nata; Puthpongsiriporn, Thunwita Sirivorapat; Kerdyam, Nittaya; Srinongwa, Prawit; Fan, Yifei; Yu, Zeyuan; Prasongporn, Pornpimon; Kacharoen, Nitchaya (Journal of Humanities and Social Sciences, Rajapruk University, 2025)
This study is documentary synthesis research with the objectives to: 1) synthesize school project management processes that align with the Sustainable Development Goals (SDGs), and 2) synthesize the factors contributing to the success and sustainability of such projects. The data were derived from project reports of three schools participating in the CONNEXT ED project, which were recognized as best practices by a private higher education institution. The tools used in the research are the record-keeping forms for each school and data analysis through content analysis. The findings revealed that: 1) the schools implemented the projects through five key processes: integration into the school curriculum, establishment of learning centers, policy formulation, incorporation of school identity, and systematic project communication; and 2) the factors contributing to the success and sustainability of the projects included school policy, leadership, collaboration among teachers and school personnel, and community involvement. These findings reflect strong alignment with several SDGs, particularly SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 17 (Partnerships for the Goals).